Determination of metals in natural waters, sediments and soils - Crompton, T. R. (Thomas Roy) (Amsterdam Elsevier, 2015)
Determination of Metals in Natural Waters, Sediments and Soils provides analytic labs with a comprehensive overview of the various methods available for analysis of metals and serves as a manual to determine metal concentrations in different media such as natural waters, waste waters, sediments and soils. The book begins with a discussion of sampling techniques and preservation and then covers metals in rivers, surface ground and mineral waters and metals in aqueous precipitation. It concludes with detailed information on analysis of metals in sediments. Determination of Metals in Natural Waters, Sediments and Soils provides a foundation for informed action by environmental interest groups and regulators and a starting point for further study by graduate students, professionals, and researchers.--Provided by publisher.
Metal in Natural Water Samples -- Sample Preservation -- Metals in River Water -- Metals in Surface, Ground, and Mineral Waters -- Metals in Aqueous Precipitation -- Analysis of Metals in Sediments -- Metals in Sediments -- Determination of Metals in Soils.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Metals -- Environmental aspects; Water -- Pollution; Soil pollution; Electronic books